Generation of Tumor-Specific Cytotoxic T Cells From Blood via In Vitro Expansion Using Autologous Dendritic Cells Pulsed With Neoantigen-Coupled Microbeads - Kiessling, Adela; Ramanathan, Keerthana; Nilsson, Ola B.; Notari, Luigi; Renken, Stefanie; Kiessling, Rolf; Grönlund, Hans; Wickström, Stina L. (Frontiers in Oncology, 2022)
For the past decade, adoptive cell therapy including tumor infiltrating lymphocytes, genetically modified cytotoxic lymphocytes expressing a chimeric antigen receptor or a novel T cell receptor has revolutionized the treatment of many cancers. Progress within exome sequencing and neoantigen prediction technologies provides opportunities for further development of personalized immunotherapies. In this study, we present a novel strategy to deliver in silico predicted neoantigens to autologous dendritic cells (DC) using paramagnetic beads (EpiTCer beads). DC pulsed with EpiTCer beads are superior in enriching for healthy donor and patient blood derived tumor specific CD8+ T cells compared to DC loaded with whole-tumor lysate or 9mer neoantigen peptides. A dose dependent effect was observed, with higher EpiTCer bead per DC being favorable. We concluded that CD8+ T cells enriched by DC loaded with EpiTCer beads are tumor specific with limited tumor cross-reactivity and low recognition of autologous non-activated monocytes or CD8+ T cells. Furthermore, tumor specificity and recognition were improved and preserved after additional expansion using our a GMP compatible rapid expansion protocol. Phenotypic analysis of patient derived EpiTCer DC expanded CD8+ T cells revealed efficient maturation, with high frequencies of central memory and effector memory T cells, similar to those observed in autologous expanded tumor infiltrating lymphocytes. These results indicate that DC pulsed with EpiTCer beads enrich for a T cell population with high capacity of tumor recognition and elimination which are features needed for a T cell product to be used for personalized adoptive cell therapy.